Greenland, Nunatak Glacier at Geologist Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fiord region of East Greenland, Nunatak Glacier from the South (head of Geologist Fiord) July 25, 1931. See AG.S. Sp. Publ. 18, pl VIIa